The Road to Democracy in South Africa. Volume 3, International solidarity, Part 1. - South African Democracy Education Trust (Routledge, 2025)
This book covers the contributions of various international organisations, governments and their peoples, and solidarity organisations to the liberation struggle in South Africa. With emphasis on international solidarity with the liberation struggle, the subject matter in this book examines and analyses the events leading to the settlement of democracy in South Africa with a focus on: the events leading to the banning of the liberation movements; the various strategies and tactics adopted in pursuit of the democratic struggle; and the events leading to the advent of democracy Print editions not for sale in Sub-Saharan Africa. This book is part of Routledge's co-published series 30 Years of Democracy in South Africa, in collaboration with UNISA Press, which reflects on the past years of a democratic South Africa and assesses the future opportunities and challenges.
Keywords: HISTORY / Africa / South / South Africa; Government, Resistance to -- South Africa -- History -- 20th century; National liberation movements -- South Africa -- History -- 20th century; South Africa -- Politics and government -- 1948-1994.